Diseksi Aorta Stanford B Debakey III dengan Pendekatan Thoracic Endovascular Aortic Repair (TEVAR) - Tangkilisan, Adrian; Sukanto, Wega; Paat, Rigel; Iskandar, Edward (Medical Scope Journal, 2025)
Abstract: Aortic dissection is a rare but highly fatal medical condition characterized by a tear in the tunica intima of the aortic wall. Most aortic dissection cases go undetected during the patient’s initial visit to the emergency department, with accurate early diagnosis rates ranging from 15% to 43%. Without immediate intervention, the mortality rate can reach 50% within the first two days. This study presents a case of aortic dissection classified as Stanford type B and DeBakey type III, managed with TEVAR. A 62-year-old male presented to the cardiothoracic surgery outpatient clinic with complaints of tearing chest pain persisting for the past month. The patient had a history of smoking and hypertension. Physical examination was within normal limits, but blood tests showed elevated leukocytes. A chest X-ray and CT angiography, followed by 3D aortic visualization, revealed an aortic dissection classified as Stanford type B and DeBakey type III. Definitive surgery was performed using TEVAR, followed by a chimney technique to seal the primary lesion in zone III of the aorta. Postoperative follow-up showed gradual improvement of chest pain symptoms. TEVAR is indicated for tears in the aortic arch area with a high risk of complications, aimung to restore flow in the true lumen and support aortic remodeling. In conclusion, in this case chronic aortic dissection results from secondary lifestyle-related risk factors and comorbidity. The Stanford and DeBakey classifications aid in aortic zoning, facilitating definitive TEVAR procedures. Keywords: aortic dissection; thoracic endovascular aortic repair Abstrak: Diseksi aorta merupakan kondisi medis langka namun memiliki tingkat mortalitas tinggi, ditandai dengan robekan pada tunika intima dari dinding aorta. Umumnya kasus diseksi aorta tidak terdeteksi saat pertama kali pasien datang ke unit gawat darurat. Tanpa intervensi segera, tingkat kematian bisa mencapai 50% dalam dua hari pertama. Kami melaporkan kasus seorang laki-laki usia 62 tahun datang ke poliklinik BTKV dengan keluhan nyeri dada seperti robekan sejak satu bulan terakhir. Pasien memiliki riwayat merokok dan hipertensi. Hasil pemeriksaan fisik dalam batas normal. Hasil pemeriksaan darah terdapat peningkatan leukosit. Interpretasi foto polos thoraks dan CT Angiografi yang dilanjutkan virtualisasi 3D pada aorta didapatkan diseksi aorta dengan klasifikasi Stanford B dan DeBakey III. Tindakan yang dilakukan ialah pembedahan definitif TEVAR yang dilanjutkan prosedur Chimney untuk menutup lesi primer pada zona III aorta. Pada follow-up pasca tindakan didapatlkan bahwa keluhan nyeri dada yang dirasakan oleh pasien sebelumnya mulai berkurang secara perlahan. Tatalaksana TEVAR merupakan indikasi pada robekan di area arkus aorta dengan komplikasi tinggi dengan tujuan untuk memperbaiki aliran true lumen dan mendukung remodeling aorta. Simpulan kasus ini ialah diseksi aorta kronis terjadi akibat faktor risiko gaya hidup sekunder dan komorbid. Klasifikasi Stanford dan DeBakey membantu proses zonasi aorta untuk prosedur definitif TEVAR. Kata kunci: diseksi aorta; thoracic endovascular aortic repair